2022
DOI: 10.1177/22799036221129373
|View full text |Cite
|
Sign up to set email alerts
|

Rabies prevention and control practices and associated factors among dog owners in Chiro, West Hararghe, Ethiopia

Abstract: Background: Rabies is among the most deadly and fatal diseases of all human diseases, once clinical symptoms appear. In developing countries, including Ethiopia, rabies prevention and control practices is not adequate. The study aimed to assess knowledge, attitude, and practices toward rabies prevention and control and identified factors associated with prevention and control practices. Methods: A community-based cross-sectional study was conducted from July 30 to August 30, 2021. A total of 326 dog-owner hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 22 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…of dog owners vaccinated their dogs in Chiro town, West Hararghe, Oromia region, Ethiopia [31]. The result of the recent study was greater than the study conducted in Jima [27].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…of dog owners vaccinated their dogs in Chiro town, West Hararghe, Oromia region, Ethiopia [31]. The result of the recent study was greater than the study conducted in Jima [27].…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, a high percent of study participants who vaccinate their dogs was reported from different studies conducted: 79% in Mekelle City, Ethiopia [29], and 71.1% in Adigrat Town, Tigray Regional State [30]. 85.3% of dog owners vaccinated their dogs in Chiro town, West Hararghe, Oromia region, Ethiopia [31]. The result of the recent study was greater than the study conducted in Jima [27].…”
Section: Discussionmentioning
confidence: 99%
“…Except for a study by Kabeta et al ( 49 ) that was carried out among dog bite victims attending Jimma Town anti-rabies Health Center located in the Oromia region, the remaining 26 studies were conducted in the community ( 20 , 28–31 , 33–48 , 50–54 ). Twelve of the studies were published in the previous five years (2018–2023 Gregorian Calendar) ( 28 , 30 , 31 , 34–36 , 38 , 40 , 42 , 47 , 48 , 52 ). Eleven of the studies were conducted in the Amhara region ( 20 , 28 , 31 , 35 , 39 , 41 , 44 , 45 , 47 , 51 , 52 ), 9 in the Oromia region ( 29 , 30 , 33 , 38 , 42 , 46 , 49 , 50 ); 3 in Addis Ababa the capital of Ethiopia’s ( 37 , 43 , 53 ); 2 in the Southern Nations, Nationalities, and Peoples’ Region (SNNPR) ( 34 , 54 ), 1 each in Tigray ( 40 ), and Somalia ( 36 ) regions.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of the studies were published in the previous five years (2018–2023 Gregorian Calendar) ( 28 , 30 , 31 , 34–36 , 38 , 40 , 42 , 47 , 48 , 52 ). Eleven of the studies were conducted in the Amhara region ( 20 , 28 , 31 , 35 , 39 , 41 , 44 , 45 , 47 , 51 , 52 ), 9 in the Oromia region ( 29 , 30 , 33 , 38 , 42 , 46 , 49 , 50 ); 3 in Addis Ababa the capital of Ethiopia’s ( 37 , 43 , 53 ); 2 in the Southern Nations, Nationalities, and Peoples’ Region (SNNPR) ( 34 , 54 ), 1 each in Tigray ( 40 ), and Somalia ( 36 ) regions. The individual study estimates range from 7.50% ( 39 ) to 99.25% ( 51 ) for a good level of knowledge about rabies, 12.55% ( 53 ) to 95.57% ( 49 ) for a favorable level of attitudes, and 4.69% ( 52 ) to 85.68% ( 28 ) for a good level of practices towards rabies prevention ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation